Lionboy / : the Truth, 3 - Corder, Zizou (Lion Boy trilogy, 2005)
Catspeaker Charlie Ashanti finds himself on a boat to the Caribbean where he will be sold to the Corporacy, but his parents and lion friends are in pursuit, and he is determined to outwit his captors.